SOME ORGANIC CONSTITUENTS OF FINS OF THE CAT-FISH, WALLAGO ATTU (BL. AND SHN.) - Saraswat, R C; Ram, Newton (Indian Journal of Fisheries, 2011)
Crude fat, total nitrogen and crude protein of whole fins of the cat-fish Wallagoattu have been studied with reference to different growth stages. All the three constituentsincrease at the growth stage II, while they decrease at the stage III. At stagesI and II thirteen amino acids and at stage III sixteen amino acids of the collagen group arepresent. At stages I and III glycine and glutamic acid are in traces. Though the variationsare marked they are not regular.